On the nonminimal vector coupling in the Duffin-Kemmer-Petiau theory and the confinement of massive bosons by a linear potential - Cardoso, T. R. [UNESP]; Castro, L. B. [UNESP]; de Castro, A. S. [UNESP] (Iop Publishing Ltd, 2010)
The vector couplings in the Duffin-Kemmer-Petiau (DKP) theory have been revised. It is shown that minimal and nonminimal vector potentials behave differently under charge-conjugation and time-reversal transformations. In particular, it is shown that nonminimal vector potentials have been erroneously applied to the description of elastic meson-nucleus scatterings and that the space component of the nonminimal vector potential plays a crucial role for the confinement of bosons. The DKP equation with nonminimal vector linear potentials is mapped into the nonrelativistic harmonic oscillator problem and the behavior of the solutions for this sort of DKP oscillator is discussed in detail. Furthermore, the absence of Klein's paradox and the localization of bosons in the presence of nonminimal vector interactions are discussed.